PERBEDAAN HASIL BELAJAR EKONOMI SISWA MELALUI PENERAPAN STRATEGI BRAIN STORMING DISERTAI SPEED TEST DIBANDINGKAN DENGAN PEMBELAJARAN KONVENSIONAL PADA SISWA KELAS X SMAN NEGERI 11 PADANG - Desmiyenti, Desmiyenti; Armiati, Armiati; Dahen, Lovelly Dwinda (Pendidikan Ekonomi, 2014)
ABSTRACTÂ This research was motivated by the low economic learning outcomes of students of class X SMA N 11 Champaign Academic Year 2013/2014. This is caused by the lack of activity of students in the learning process. This study aims to determine the differences in economic activity and the learning outcomes of students with implementation strategies accompanied Speed Test Brain Storming with conventional learning in class X SMAN 11 Padang .This research is an experimental study. The study population is a student of class X SMA N 11 Champaign school year 2013/2014. Samples were taken by purposive sampling technique, was chosen as the experimental class X8 class and class X2 as the control class. The instrument used is the observation sheet student activity and achievement test. Data analysis techniques to test the hypothesis is to test Z.Based on the analysis of data obtained an average value of 83.87 experimental class and control class average of 75.88. The results of data analysis known Z count value is greater than 3.038 price 1.960 Z table which means the hypothesis is accepted at significance level Î±=0.05. It can be concluded that the learning outcomes of students with the application of economic strategy with Speed Test Brain Storming better than economics student learning outcomes in the conventional learning process in class X SMA N 11 Padang.